ENGAGING STUDENTS BY USINGHUMOROUS VIDEO ADS IN ENGLISH LISTENING SKILL SUBJECT : A Case Study at an Academy of Secretary in West Java, Indonesia - Hendrawan, Wawan (2012)
This research investigated the use of humorous video ads in the English listening skill subject. The foci of the investigation were firstly to reveal how the humorous video ads engaged the students in the English listening skill subject and secondly to know the disadvantages and advantages of using the humorous video ads as perceived by the students in the English listening skill subject.The research was conducted at one academy of secretary in Bandung, West Java-Indonesia, involving nine fourth-semester students. A case study design was used in this research and data were obtained through observations, questionnaires and interviews. The data from these three instruments were analyzed and interpreted qualitatively. Finally, triangulation was applied to increase the validity of the research.The research revealed that the humorous video ads engaged the students in the English listening skill subject. This was proven by the fulfillment of all characteristics of student engagement (Jones, 2009) such as positive body language, consistent focus or attention, fun and excitement, verbal participation, and student confidence. Yet, some disadvantages were found. The disadvantages were problems related to the implementation of the humorous video ads in the English listening skill subject. The problems embraced the students' difficulties of understanding the messages, colloquial language, accents, video display, topics and background knowledge. The problems also included the students' difficulties of grasping the speed of delivery and knowing the vocabulary. By contrast, some advantages were identified, namely developing the ability to think critically, improving listening skill, stimulating language production, adding vocabulary, understanding other cultures, understanding verbal expressions through video display, having fun, and being excited and motivated to learn English. There were three implications resulting from this research. First, this research reduced the problems of engagement like affective and habitual problems possessed by the students in the English listening skill subject. This suggested that the humorous video ads were suitable to use as teaching materials. Second, the disadvantages which were found indicated that the humorous video ads presented in the English listening skill subject should be selected carefully in order to avoid problems addressed before. Third, the advantageous aspects which were found demonstrated that the humorous video ads gave positive results to the students' learning process both cognitively and affectively.Based on these implications, the humorous video adshad a great impact on the teaching and learning process in the English listening skill subject.Keywords: humor, video, engagement, English listening skill